Adipocyte Apoptosis Following a Novel Method for Double Chin Reduction: A Pilot Human Histology Study - Goldberg, David J. (Journal of cosmetic dermatology, 2025)
ABSTRACT Background Submental fullness is perceived as unattractive by both men and women. The noninvasive simultaneous delivery of HIFES and synchronized radiofrequency+ (Sync RF+) technologies aims to address the submental fullness by concurrently targeting the skin, adipose tissue, and weakened anterior belly of the digastric muscle, the three contributing layers to the double chin appearance. Aims This study aims to investigate the histological changes to adipose tissue related to cell morphology, caspase‐7, and Bcl‐2 levels to detect adipocyte apoptosis following the HIFES and Sync RF+ treatment on human subjects. Methods The active group (n = 6) received single 20‐min treatment on the submental area, while the control group (n = 2) did not receive any treatment. Biopsies of subcutaneous fat tissue were obtained at baseline, and 24 h and 7 days posttreatment. The specimens were histologically and immunohistochemically analyzed for changes in morphology, caspase‐7, and Bcl‐2 levels. Results Observed caspase‐7 levels increased by 511% at 24‐h posttreatment, and 101% at 7 days (p < 0.0001), while the Bcl‐2 levels decreased by 89% at 24 h and 24% at 7 days posttreatment (p < 0.0001). The control group had no statistically significant relative changes in the activity of caspase‐7. Posttreatment adipocytes were shrunken in size, and shapes lost their uniformity compared to baseline. Five of six subjects reported the treatment as being comfortable. No adverse events were observed during the study. Conclusions The results of this human histology study indicate that noninvasive HIFES and Sync RF+ technologies have a favorable safety profile for submental fat reduction through the induction of adipocyte apoptosis. Trial Registration ClinicalTrials.gov identifier: NCT06282172